2013
DOI: 10.17705/1jais.00338
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Using Carbon Management Systems to Promote Ecologically Responsible Behaviors

Abstract: With the hope of mitigating the harmful impacts of climate change, many organizations are taking actions to reduce their carbon footprints. Carbon-reducing initiatives in organizations are varied: they range from green product innovations to encouraging behavioral changes by customers and employees. Green IS can play an important role in environmental sustainability by supporting a number of these strategies. Drawing on theories of persuasive systems design, this paper explores how one category of Green IS, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 67 publications
1
45
0
Order By: Relevance
“…The results of this search revealed that, except for two papers (e.g., Corbett (2013) and one paper published in the special issue (Loock et al 2013)), the few green IS papers accepted for top journals were conceptual or analytical in nature. In Table A1, we critically overview each paper and indicate where the research might go if it focused more on solutions.…”
Section: Green Is Research (2013-2016)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this search revealed that, except for two papers (e.g., Corbett (2013) and one paper published in the special issue (Loock et al 2013)), the few green IS papers accepted for top journals were conceptual or analytical in nature. In Table A1, we critically overview each paper and indicate where the research might go if it focused more on solutions.…”
Section: Green Is Research (2013-2016)mentioning
confidence: 99%
“…In Table A1, we critically overview each paper and indicate where the research might go if it focused more on solutions. Corbett (2013) This paper investigates how to design and develop carbon management systems (CMS) that persuade employees to develop pro-environmental behavior. It identifies eight new design principles including two related to task support; namely, commitment and personal learning.…”
Section: Green Is Research (2013-2016)mentioning
confidence: 99%
“…The holistic view on economic, ecological and social aspects is, however, rarely observed in the literature. Articles in the review range from tackling only a single ecological dimension [7], [9], [49], [53], [13], [45], [51], [55], to attributing the same degree of importance to each of them [4].…”
Section: Sustainability Focus (2)mentioning
confidence: 99%
“…Among the addressed ecological problems are reducing the global carbon footprint [7], [14], [48], waste reduction [8], [11], [16] and resource consumption optimization [9], [13], [55].…”
Section: Sustainability Focus (2)mentioning
confidence: 99%
See 1 more Smart Citation